1997
DOI: 10.2166/wst.1997.0718
|View full text |Cite
|
Sign up to set email alerts
|

UV ability to inactivate microorganisms combined with factors affecting radiation

Abstract: In the present study, the effect of UV radiation on the inactivation of a range of microorganisms was studied. Each organism was seeded into sterile tap water and exposed to UV in batch experiments with changing turbidities. In addition, the effect of UV on microbial communities in river Nile water was examined. It was found that 1min contact time (0.5L/min flow rate) was effective against vegetative cells levels almost reaching zero (except with Staphylococcus aureus). On the other hand, spore-forming bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…These results are in agreement with the findings of other workers (Onaolapo, 1995). Shaban et al(1997) and Newcombe et al(2005) found that Staphylococcus and spore-forming Bacillus were more resistant to UV than the other vegetative bacteria. Ajaz et al(2004) screened 4 phenol resistant bacteria strains, two of which belong to genera Staphylococcus and Bacillus.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the findings of other workers (Onaolapo, 1995). Shaban et al(1997) and Newcombe et al(2005) found that Staphylococcus and spore-forming Bacillus were more resistant to UV than the other vegetative bacteria. Ajaz et al(2004) screened 4 phenol resistant bacteria strains, two of which belong to genera Staphylococcus and Bacillus.…”
Section: Discussionsupporting
confidence: 93%
“…This value is less than the 5 mg L −1 TSS value, which is known to reduce Field investigation of advanced oxidation of secondary effluent 2051 the effectiveness of UV inactivation. [7,34] The color ranged from 40-50 hazen units, and the mean particle size of the sample was 30 µm with 86% greater than 10 µm. Assuming most of the color was attributed to organic substances, one can assert that absorption of UV photons by the organic matter in the secondary effluent had taken place during the irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of UV disinfection in water and wastewater treatment systems have increased in recent years in Canada. Numerous research has been carried out to find the correlations between water quality, bacterial sensitivity and UV disinfection efficiency [10]- [12], the impact of cold temperatures on UV disinfection processes, especially, the responses of the pathogenic microorganisms after experiencing freezing to UV is however seldom examined [13], [14]. As a treatment alternative, natural or mechanical freezing has been used for various water or wastewater treatment, sludge pre-treatment or conditioning, and desalination [15]- [19].…”
Section: Introductionmentioning
confidence: 99%